Phylogenetic inference of Ericales based on plastid genomes and implication of cp-SSRs - Anjan Hazra; Subhanwita Das; Senjuti Bhattacharya; Susmita Sur; Chandan Sengupta; Sauren Das (BioTechnologia, 2021)
Ericales is an ancient eudicot order encompassing numerous species of economic and ornamental values. Despite several phylogenomic studies, the evolutionary relationship among certain families of this group remains uncertain. The present study assessed a multilocus species tree of Ericales based on 107 chloroplast genomes. The plastome derived microsatellite motifs were also simultaneously explored to check their dynamicity in corroboration of species phylogeny and systematics. In addition to resolving the usual hierarchy, the present phylogenetic analysis enabled to resolve the persisting lineage disparity with valid statistical support. Accordingly, divergence incongruences of Primulaceae, Ebenaceae, and Sapotaceae from earlier reports were reinstated in presently inferred phylogeny, which further supported the latest transcriptome-based relationship of the corresponding group. Various SSR motif characteristics emerged following the recognition of the evolutionary pathway. Numerical variation in tetranucleotide repeats showed even intraspecific or varietal differences in Camellia sinensis. Validation of plastome microsatellite-based polymorphism among the related taxa might pave the way for future phylogenetic and population studies of this economically important group.